2022
DOI: 10.1002/ijc.34373
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with interval colorectal cancer after negative FIT: Results of two screening rounds in the Dutch FIT‐based CRC screening program

Abstract: The interval colorectal cancer (CRC) rate after negative fecal immunochemical testing (FIT) is an important quality indicator of CRC screening programs. We analyzed the outcomes of two rounds of the FIT-based CRC screening program in the Netherlands, using data from individuals who participated in FIT-screening from 2014 to 2017. Data of individuals with one prior negative FIT (first round) or two prior negative FITs (first and second round) were included. Outcomes included the incidence of interval CRC in FIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…This may affect the results if the FIT is more sensitive (compared with gFOBT) to left-sided cancers as opposed to right sided, as right-sided cancers were more common in women. 31 In the Dutch screening programme where the FIT is also employed, a higher incidence rate of interval cancers was seen in males compared with females 32 comparable to what we found. Regardless of which FIT positivity threshold is applied in screening, some cancers and precursor lesion will be missed.…”
Section: Discussionsupporting
confidence: 86%
“…This may affect the results if the FIT is more sensitive (compared with gFOBT) to left-sided cancers as opposed to right sided, as right-sided cancers were more common in women. 31 In the Dutch screening programme where the FIT is also employed, a higher incidence rate of interval cancers was seen in males compared with females 32 comparable to what we found. Regardless of which FIT positivity threshold is applied in screening, some cancers and precursor lesion will be missed.…”
Section: Discussionsupporting
confidence: 86%
“…The design of our study is xed and based on the current test (FIT; FOB-Gold; Sentinel Diagnostics, Milan, Italy), cut-off (47 μg Hb/g feces) and age range (individuals aged 55-75) used in the Dutch CRC screening program. Nevertheless, even if the CRC screening program would be modi ed in terms of test, cut-off or age range, we expect that the results of our study are still relevant: the effect of the risk factor f-Hb holds for all ages, and the literature shows that it also holds for other cut-offs and FIT brands [7,11,[13][14][15][16][17][30][31][32]. Furthermore, even if the decision should be made to use another test instead of FIT, the study is still informative on the acceptability of risk-based screening in general.…”
Section: Discussionmentioning
confidence: 85%
“…Sex and age are also automatically registered, but their predictive value is much lower than the f-Hb concentration (odds ratios for AN: 1.6 (male sex) and 0.9-1.1 (increasing age) vs. 2.5-21.8 (increasing f-Hb concentrations), respectively [7]). In addition, a strong association was observed between the measured f-Hb concentration in participants with a negative FIT and the risk of developing interval CRC in the Dutch CRC screening program [11]. Interval CRC is de ned as CRC diagnosed after a negative FIT and before invitation to the next screening round [12].…”
Section: Introductionmentioning
confidence: 99%
“…A second hypothesis could be that due to the distribution of blood throughout the formed stool also reduces the concentration of haemoglobin 8. Finally, most of the advanced serrated lesions are right sided and tend to bleed less than advanced adenomas 25. This may partly explain the missed CRC rate within our cohort since 50% (n=4) of missed CRC were right-sided tumours.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, findings from previous studies have suggested that FIT sensitivity is higher for left-sided CRCs and that right-sided lesions are more frequently missed by FIT 8 24 25. For instance, a recent UK study by Cunin et al looking at symptomatic patients undergoing FIT on a CRC pathway reported that of seven FIT <10 patients, six were right-sided (caecal) tumours, suggesting that the nature and biology of these tumours may play a role in their FIT sensitivity 24.…”
Section: Discussionmentioning
confidence: 99%